COOPERATIVES IN SERBIA – EVOLUTION AND CURRENT ISSUES - Chroneos Kresavac, Biljana; Petković, Goran (Economics of Agriculture, 2015)
Cooperatives in Serbia have long history, evolving from big traditional families to the contemporary social networked organizations and even private companies acting like coops. Current legal framework, on one side, enables many possibilities, but on the other side prevents further development of cooperatives. An interview of key players in the coop sector was one of the research methods. Other methods include historical method, comparative analysis method and case study method. In conclusion, the major obstacle for the further coops development in Serbia is legal status of ownership. Other obstacles are: the level of state interference, the loyalty of primary producers and participants, the average land size per households, etc. The paper includes three parts: historical evolution, successful case study and framework for future development.